Effect of Pyrolysis Temperature on Polycyclic Aromatic Hydrocarbon (PAH) and Organic Acid Compounds From Oil Palm Shell Liquid Smoke - Tamrin, Tamrin (Journal of Chemical Natural Resources, 2020)
The effect of pyrolysis temperature on polycyclic aromatic hydrocarbon and organic acid compounds from oil palm shell liquid smoke has been successfully conducted. In this study, variations of temperature were used at 600 to 950ÂºC with temperature intervals at 50ÂºC. Liquid smokes obtained were characterized using GC-MS and FTIR. The GC-MS and FT-IR analysis results showed the presence of organic acid compounds such as acetic acid and propanoic acid. In contrast, no found polycyclic aromatic hydrocarbons (PAH) compounds. The higher the pyrolysis temperature involved the higher the organic acid contents.